Cotinine levels influence the risk of rupture of brain aneurysms. (3rd August 2022) - Missori, Paolo; de Sousa, Diana Aguiar; Ambrosone, Angela; Currà, Antonio; Paolini, Sergio; Incarbone, Giorgio; Amabile, Elena; Biraschi, Francesco; Diana, Francesco; Peschillo, Simone
Abstract : Cotinine, the primary metabolite of nicotine, is currently regarded as the best biomarker of tobacco smoke exposure. We aim to assess whether cotinine levels are associated with (1) intracranial aneurysm and (2) intracranial aneurysm rupture. Methods: We performed a single‐center case–control study. Cases were consecutive patients admitted with diagnosis of brain aneurysm (ruptured or unruptured). We randomly selected controls without intracranial aneurysm from the same source population that produced the cases. Smoking data were collected by questionnaire, and serum levels of cotinine were used as an objective measure of nicotine exposure. Logistic regression models were used to assess the relationship between cotinine levels and aneurysm rupture. Results: We included 86 patients with intracranial aneurysm and 96 controls. Smoking status ( p  < .001), cotinine levels ( p  = .009), and female sex ( p  = .006) were associated with diagnosis of intracranial aneurysm. In the multivariate analysis, controlling for sex, smoker status and age, levels of cotinine were independently associated with aneurysm rupture (OR 1.53, 95% CI 1.10–2.13, p  = .012). Conclusions: Our results suggest that high cotinine levels in smokers with brain aneurysm are significantly associated with high rupture risk, independently of smoker status, age, and sex.